2018
DOI: 10.12688/f1000research.16537.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding and managing rosacea

Abstract: Rosacea is a common chronic inflammatory skin disease of the central facial skin and is of unknown origin. Currently, two classifications of rosacea exist that are based on either “preformed” clinical subtypes (erythematotelangiectatic, papulopustular, phymatous, and ocular) or patient-tailored analysis of the presented rosacea phenotype. Rosacea etiology and pathophysiology are poorly understood. However, recent findings indicate that genetic and environmental components can trigger rosacea initiation and agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
173
0
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(194 citation statements)
references
References 91 publications
(88 reference statements)
3
173
0
18
Order By: Relevance
“…16 Several approaches of anti-inflammation and anti-angiogenesis treatment improve the symptoms. [17][18][19][20] Previous reports have shown an association between rosacea and numerous systemic diseases, such as cardiovascular, gastrointestinal, neurological and autoimmune diseases, and cancers. 21 Our results have confirmed that breast cancer and hypertension may be associated with rosacea in females.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several approaches of anti-inflammation and anti-angiogenesis treatment improve the symptoms. [17][18][19][20] Previous reports have shown an association between rosacea and numerous systemic diseases, such as cardiovascular, gastrointestinal, neurological and autoimmune diseases, and cancers. 21 Our results have confirmed that breast cancer and hypertension may be associated with rosacea in females.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this split-face study confirm the clinical benefit of M89 in subjects with rosacea with erythema and sensitive skin to reinforce the natural defences of the skin in restoring the natural skin barrier, stimulating antioxidant activity and reducing inflammation, commonly observed in subjects with rosacea. [18][19][20][21][22][23][24][25]31 Daily use of M89 led to a significant improvement of erythema, skin tightness and skin dryness sensations after 15 and 30 days of treatment compared to usual skin care products. Similarly, statistically significant decreases in the mean basal scores of skin sensitivity, detected by means of a sting-test, were recorded after 15 and 30 days of treatment with M89, although no statistically significant variation was recorded in the same parameter after the treatment with the usual skin care product.…”
Section: Discussionmentioning
confidence: 99%
“…These minerals reinforce the natural defences of the skin in restoring the natural skin barrier, stimulating antioxidant activity and reducing inflammation, commonly observed in subjects with rosacea. [18][19][20][21][22][23][24][25] In an unpublished analysis of a global investigation concerning a subgroup of subjects with mild rosacea, M89 applied daily on the face improved clinical signs of rosacea and, according to subjects, improved their symptoms as well as skin hydration, indicating that M89 may strengthen the natural skin barrier and help to protect the skin from environmental and external aggressions. 26 The aim of our split-face study was to assess the clinical benefit of M89 compared to standard skin care in subjects with rosacea with erythema and sensitive skin after 30 days of daily use.…”
Section: Introductionmentioning
confidence: 99%
“…3 Females and males are equally affected, although the manifestations of the pathology may vary according to gender. 4 The highest prevalence of the pathology is found among people in the age range between 45 and 60 years. 1 Although rosacea etiology remains not completely understood, it seems to be multifactorial, comprising both a genetic predisposition and environmental factors that can promote an exaggerated vasodilation and water loss.…”
Section: Introductionmentioning
confidence: 99%
“…5 For instance, rosacea may be initiated or aggravated by several trigger factors, such as cold, heat, ultraviolet irradiation, and dermal or oral exposure to chemicals. 4 Based on morphological characteristics, rosacea may be classified into four groups: ocular, erythethematotelangiectatic, papulopustular, and phymatous. Ocular rosacea affects the periocular zone, whereas erythematotelangiectatic, phytamous and papulopustular rosacea arise in the middle of the face and they primarily include telangiectasia, erythema, and flushing.…”
Section: Introductionmentioning
confidence: 99%